Development of assessment instruments on limb and sensory materials based on the BATURADEN word wall application for elementary school students - Suprihatin*, Suprihatin; Wardhani, Sri; Lestari, Wahyu (Riwayat: Educational Journal of History and Humanities, 2024)
Assessment activities that are often used by teachers are conventional, namely, students doing written questions and students answering on answer sheets provided by the teacher. Conventional assessment has several disadvantages, namely the cost of procuring paper for doubling questions, less effective and efficient proofreading time, and errors when correcting. The purpose of the study was to develop a word wall-based assessment instrument on Body Parts and Senses material for elementary school students. This research is included in development research that modifies the research steps of Borg Gall. The method of data collection is through validation questionnaires filled out by experts using the Likert scale. While the calculation of the validity test uses Aikes's formula. Based on validation tests from material experts, linguists, media experts, and instrument experts, the BATURADEN word wall application-based assessment instrument is valid. Based on reliability tests conducted during small-scale tests, the BATURADEN word wall application-based assessment instrument was declared valid with a value of 0.758 which means it is reliable.